The role of mobile commerce service quality in enhancing consumer loyalty: A strategic business perspective - Mochamad Zevazaky Langit; Khairani Ratnasari Siregar (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The development of e-commerce in Indonesia shows significant growth, with the number of users predicted to continue to increase until 2029. This phenomenon is driven by easier internet access and the widespread use of smartphones. This study aims to analyze the effect of mobile commerce aplication (MCA) service quality on consumer loyalty intentions in Shopee e-commerce through consumer satisfaction. Methods: This research uses a quantitative method with a causal approach. Data was collected through a Google Form questionnaire distributed to 238 respondents with a sampling process using non-probability techniques with samples selected purposively. The SERVQUAL model, is adopted to evaluate MCA service quality and its influence on customer satisfaction and loyalty intention. The statistical method of partial least squares structural equation modeling (PLS-SEM) analyzed with SmartPLS 4 software and then evaluated through combined importance performance map analysis (cIPMA). Findings: The results of this study show that customer satisfaction has a positive and significant effect on customer loyalty intention. Service quality has a positive and significant effect on customer loyalty intention through customer satisfaction, including variables of information quality, personalization, reliability, and usability while assurance, responsiveness, and security do not have a positive and significant effect. Conclusion: The study concludes that customer satisfaction plays a crucial role in strengthening customer loyalty intention in Shopee’s mobile commerce. Among the examined service quality dimensions, information quality, personalization, reliability, and usability significantly enhance loyalty through satisfaction, while assurance, responsiveness, and security show no significant impact. Novelty/Originality of this article: This study offers novelty by identifying which specific dimensions of Mobile Commerce Application (MCA) service quality directly strengthen customer loyalty intention through satisfaction in the context of Shopee—revealing that only information quality, personalization, reliability, and usability have significant effects, while assurance, responsiveness, and security do not.